Analysis of Science Process Skills and Learning Outcomes In Inquiry Learning Model With Mini Research Strategy to Support Pharmacy Science in Vocational High Schools - Jiwanjaya, Yoga; Lisdiana, Lisdiana; Yuniastuti S., Ari (Journal of Innovative Science Education, 2019)
Biology subjects in Pharmacy Vocational High Schools are not yet integrated with pharmacy subjects even though biology subjects have a close relationship with pharmacy fields related to organs and medicines in the human digestive system. This research aims to analyze the science process skills and learning outcomes in the inquiry learning model with a mini research strategy as a supporting of pharmacy science in Vocational High Schools. This research uses quasy experiment research with pretest posttest control group design. Analysis of learning outcomes using the independent sample t-test, N-Gain test, and N-Gain t-test to see differences in the value of learning outcomes between the control class and the experimental class. Analysis of science process skills uses the average score of observations of science process skills. To see whether the research can supporting Vocational Pharmacy Science is analyzed using descriptive analysis of interviews with vocational productive teachers. The result of the value of learning outcomes get data that the value of learning outcomes of the experimental class is better than the control class, while the science process skills of students in the experimental class are better than the control class. Descriptive analysis of interview productive teacher shows that this study can be used as a supported of pharmacy science in Vocational High Schools. Analysis of the value of student learning outcomes, science process skills and Interview productive teacher shows that inquiry learning models with mini research strategies can support subjects related to pharmacy.